Phenotypic heterogeneity in fungi: importance and methodology - Hewitt, Sarah K.; Foster, David S.; Dyer, Paul S.; Avery, Simon V. (Elsevier, 2016)
Phenotypic heterogeneity describes the variation that exists between individual cells, spores or other biological entities within genetically-uniform populations of fungi or other organisms. Studies over the last 10–-15 years have successfully used laboratory- and modelling-based approaches to demonstrate the prevalence of phenotypic heterogeneity and characterise the molecular bases of the phenomenon (primarily centred around heterogeneous gene expression). In contrast to progress in these areas, the relevance of phenotypic heterogeneity for the competitive success of organisms in different natural scenarios, although widely speculated upon, has only recently begun to be investigated. This focus review addresses this latter question as tackled in recent studies with yeasts and filamentous fungi. We concentrate on the relevance to fungal activities such as survival against environmental stressors, pathogenesis, and spoilage. We also discuss methodologies for interrogating phenotypic heterogeneity in fungi. The emerging prevalence and apparent importance of fungal phenotypic heterogeneity provides a timely reminder that certain, potentially core aspects of fungal biology still remain widely under-explored.